Comparison of interferon-γ release assay to two cut-off points of tuberculin skin test to detect latent Mycobacterium tuberculosis infection in primary health care workers. - Fernanda Mattos de Souza (Public Library of Science (PLoS), 2014)
Background An interferon-γ release assay, QuantiFERON-TB (QFT) test, has been introduced an alternative test for the diagnosis of latent Mycobacterium tuberculosis infection (LTBI). Here, we compared the performance of QFT with tuberculin skin test (TST) measured at two different cut-off points among primary health care work (HCW) in Brazil. Methods A cross-sectional study was carried out among HCWs in four Brazilian cities with a known history of high incidence of TB. Results of the QFT were compared to TST results based on both ≥5 mm and ≥10 mm as cut-off points. Results We enrolled 632 HCWs. When the cut-off value of ≥10 mm was used, agreement between QFT and TST was 69% (k = 0.31), and when the cut-off of ≥5 mm was chosen, the agreement was 57% (k = 0.22). We investigated possible factors of discordance of TST vs QFT. Compared to the TST-/QFT- group, risk factors for discordance in the TST+/QFT- group with TST cut-off of ≥5 mm included age between 41-45 years [OR = 2.70; CI 95%: 1.32-5.51] and 46-64 years [OR = 2.04; CI 95%: 1.05-3.93], BCG scar [OR = 2.72; CI 95%: 1.40-5.25], and having worked only in primary health care [OR = 2.30; CI 95%: 1.09-4.86]. On the other hand, for the cut-off of ≥10 mm, BCG scar [OR = 2.26; CI 95%: 1.03-4.91], being a household contact of a TB patient [OR = 1.72; CI 95%: 1.01-2.92] and having had a previous TST [OR = 1.66; CI 95%: 1.05-2.62], were significantly associated with the TST+/QFT- group. No statistically significant associations were found among the TST-/QFT+ discordant group with either TST cut-off value. Conclusions Although we identified BCG vaccination to contribute to the discordance at both TST cut-off measures, the current Brazilian recommendation for the initiation of LTBI treatment, based on information gathered from medical history, TST, chest radiograph and physical examination, should not be changed.